Cancer Immunotherapy and Abnormal Lipid Metabolism - Wenxin JIANG; Peng LIU (Zhongliu Fangzhi Yanjiu)
Lipid metabolism relates to tumor proliferation, progression, and immune escape. With the rapid development of immunotherapy, the relationship between immunotherapy and lipid metabolism has been constantly explored. On the one hand, immunotherapy can cause dyslipidemia and accelerate the progression of atherosclerosis, which has been neglected by clinicians. On the other hand, lipid metabolism can affect antitumor immunity at multiple levels and potentially influence the efficacy of immunotherapy. Lipid metabolism-regulating drugs also have the potential to synergize with immunotherapy. This review summarizes relevant research evidence to inspire further exploration.